Personal values and decision: making styles of administrators in Malaysian Universities / Sazlyra Mohd Arshad ... [et al.] - Mohd Arshad, Sazlyra; Yaacob, Hashim Fauzy; Mohd Yasin, Intan Yusliyana; Syed Hamid, Sharifah Norhafiza (2010)
The study indentified personal value system of administrator and its relationship with decision making styles. Administrator completing the Rokeach Value Survey and the Rowe Decision Style Inventory. However Rokeach Value Survey Inventory was modified to develop instrument based on Malaysian local value system. Participant of this survey is a Malaysian Universities’ administrator from a selected university.